Letramento digital e a prática de alunos do lecampo em sala de aula: estudo sobre possíveis repercussões do ensino de informática básica na educação do campo - Anderson de Souza Santos (2016)
This work has as its central idea to discuss the relevance of the development of a digital literacy course for future schools in the field`s teachers, taught since 2014, for students of the Degree Course (LECAMPO) the Languages area, Arts and Literature (LAL 2014). In this regard, we tried to make a contrast between literacy and digital literacy, identifying the importance of these concepts, not only for the institution to which those students are linked, but also for society in general. The theoretical background includes studies on digital inclusion and on digital divide, multiliteracies and digital literacy, literacy theories of social and cultural nature, as well as documents addressing the relationship between education and the Peasant Movement. This study concludes that the concept of digital literacy supported by several authors surveyed opens a wide field of possibilities for the course object of this study, especially considering the viability of social inclusion through digital inclusion, but requires an ethical position towards the concept of inclusion based on the activism and the autonomy of the subjects and the existing cultural plurality in the social context to which they belong.